MENGEMBANGKAN METODE PEMIKIRAN ISLAM PENDEKATAN BAYANI, IRFANI, DAN BURHANI - Utami, Rahmi; Revi Inanda Maulana; Suci Sahpitri; Syahrul Ramadhan; Raini Suri (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
Islam's intellectual heritage, each with its characteristics of the bayani method emphasizes understanding divine texts through linguistic and normative approaches; the burhani method relies on logic and rationality as primary tools for acquiring knowledge; while the irfani method focuses more on inner experience, intuition, and spiritual illumination.This study aims to comprehensively explain the three main approaches in Islamic epistemology bayani, burhani, and irfani and to evaluate their relevance and contribution in responding to the challenges of scientific and intellectual development in contemporary Islamic thought. This study employs a qualitative approach using the library research method by examining various classical and contemporary sources relevant to describing and analyzing the three approaches. Data is collected from journals, books, and academic writings that discuss Islamic epistemology from various perspectives. The findings show that each method has its own strengths and limitations. The bayani approach is strong in legal authority and textual clarity but often lacks responsiveness to social changes. The burhani approach is highly rational and analytical but tends to overlook spiritual aspects. The irfani approach, on the other hand, offers profound insight into inner and esoteric dimensions, yet remains subjective and difficult to verify. Therefore, integrating the three is deemed essential to forming a holistic, contextual, and balanced Islamic scientific framework that unites text, reason, and spiritual insight. This study concludes that the synergy among the bayani, burhani, and irfani methods not only enriches the Islamic intellectual tradition but also contributes significantly to the development of Islamic education, law, and thought that are responsive to contemporary realities.